Perspectives on Nature Conservation Patterns, Pressures and Prospects - Tiefenbacher, John (IntechOpen, 2012)
Perspectives on Nature Conservation demonstrates the diversity of information and viewpoints that are critical for appreciating the gaps and weaknesses in local, regional and hemispheric ecologies, and also for understanding the limitations and barriers to accomplishing critical nature conservation projects. The book is organized to emphasize the linkages between the geographic foci of conservation projects and the biological substances that we conceptualize as "nature", through original research. The reader moves through perspectives of diminishing spatial scales, from smaller to larger landscapes or larger portions of the Earth, to learn that the range of factors that promote or prevent conservation through the application of scholarship and academic concepts change with the space in question. The book reflects disciplinary diversity and a co-mingling of science and social science to promote understanding of the patterns of, pressures on and prospects for conservation.